Electrical effective parameters of the grains and the Montgomery's method in Bi 1.65Pb 0.35Sr 2Ca 2.5Cu 3.5O y ceramics - Cruz García, A. (2018)
In this paper we have applied the Montgomery's measurement method to Bi 1.65Pb 0.35Sr 2Ca 2.5Cu 3.5O y ceramic samples, to study the behavior of the grains? electrical effective parameters, such as: intrinsic effective anisotropy, t= ρc/ ρa b, the slope of the linear part in the temperature dependence of the ab-planes resistivity, Aa b= Δρa b/ ΔT, the weak links resistivity, ρw l, and the orientation probability of the grains? a-axes along a certain preferential direction, γx a. Here, ρa b, ρc and T are the main values of the resistivitity tensor and the measurement temperature, respectively. The samples were pressed uniaxially at three different compacting pressures and extracted from the pellets by cutting an slab along the cylinder axis. Samples cut in this way, exhibit almost an isotropic behavior in the transport properties. Moreover, the sample extracted from the pellet compacted at 488 MPa exhibits the best inter and intragranular properties. The effective intrinsic anisotropy of its grains has the lowest value in the sample set. These results can be used in the fabrication of this superconducting material for certain applications.